A blubber gene expression index for evaluating stress in marine mammals. Issue 1 (8th September 2020) - Pujade Busqueta, Laura; Crocker, Daniel E; Champagne, Cory D; McCormley, Molly C; Deyarmin, Jared S; Houser, Dorian S; Khudyakov, Jane I
Abstract : Blood hormone levels are often used to measure stress in animals, but blood cannot be sampled from many large, wild marine mammals. Gene expression in blubber, which can be sampled more easily, is correlated with blood cortisol and thyroid hormones, providing an alternative way to measure stress in marine mammals. Abstract: Evaluating the impacts of anthropogenic disturbance on free-ranging marine mammal populations, many of which are in decline, requires robust diagnostic markers of physiological stress and health. However, circulating levels of canonical 'stress hormones' such as glucocorticoids, which are commonly used to evaluate animal health, do not capture the complexity of species-specific responses and cannot be easily measured in large, fully aquatic marine mammals. Alternatively, expression of stress-responsive genes in hormone target tissues such as blubber, the specialized subcutaneous adipose tissue that can be manually or remotely sampled from many marine mammals, may be a more informative and sensitive indicator of recent (within 24 h) exposure to stressors. We previously identified genes that were upregulated in the inner blubber of juvenile northern elephant seals during experimental stimulation of the hypothalamic–pituitary–adrenal axis. In this study, we measured baseline expression levels of a subset of these genes in inner blubber of unmanipulated juvenile elephant seals of varying physiological states and correlated them with other stress markers (body condition index, corticosteroid and thyroid hormone levels). Expression of 10 genes, including those associated with lipid metabolism ( ACSL1, HMGCS2, CDO1 ), redox homeostasis ( GPX3 ), adipokine signaling ( ADIPOQ ), lipid droplet formation ( PLIN1, CIDEA ) and adipogenesis ( DKK1, AZGP1, TGFBI ), was described by three principal components and was associated with cortisol and thyroid hormone levels. Significantly, baseline gene expression levels were predictive of circulating hormone levels, suggesting that these markers may be potential indicators of exposure to stressors in marine mammal species that are inaccessible for blood sampling. A similar approach may be used to identify species-specific stress markers in other tissues that can be sampled by remote biopsy dart from free-ranging marine mammals, such as outer blubber and skin.